2021
DOI: 10.34172/apb.2023.019
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis as a Potential Cell Death Mechanism against Cisplatin-Resistant Lung Cancer Cell Line

Abstract: Purpose: Drug resistance is a challenging issue in cancer chemotherapy. Cell death induction is one of the main strategies to overcome chemotherapy resistance. Notably, ferroptosis has been considered a critical cell death mechanism in recent years. Accordingly, in this study, the different cell death strategies focused on ferroptosis have been utilized to overcome cisplatin resistance in an in vitro lung cancer model. Methods: The physiological functions of Akt1 and GPX4, as critical targets for ferroptosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…By accelerating ferroptosis progress, the development of lung cancer can be suppressed, while the drug resistance and radiation resistance of lung cancer is also resisted to a certain extent ( Mou et al, 2019 ). Studies have shown that achieving ferroptosis increases ROS levels in cells and the cytotoxicity of cisplatin ( Golbashirzadeh et al, 2023 ). Nevertheless, osimertinib-resistant cells are prone to ferroptosis due to raised accumulation of ferrous ions ( Konishi et al, 2023 ).…”
Section: Biological Compounds Improve Lung Cancer Drug Resistance Thr...mentioning
confidence: 99%
“…By accelerating ferroptosis progress, the development of lung cancer can be suppressed, while the drug resistance and radiation resistance of lung cancer is also resisted to a certain extent ( Mou et al, 2019 ). Studies have shown that achieving ferroptosis increases ROS levels in cells and the cytotoxicity of cisplatin ( Golbashirzadeh et al, 2023 ). Nevertheless, osimertinib-resistant cells are prone to ferroptosis due to raised accumulation of ferrous ions ( Konishi et al, 2023 ).…”
Section: Biological Compounds Improve Lung Cancer Drug Resistance Thr...mentioning
confidence: 99%
“…In addition, etoposide-mediated metabolic reprogramming can increase lactate production in NSCLC cells, leading to GPX4 ubiquitination and ferroptosis resistance [ 99 ]. Ferroptosis stimulation via GPX4 knockdown or FIN56 administration can eliminate chemoresistant NSCLC cells [ 100 ]. In line with this, it has been shown that KLF11 suppresses GPX4 in lung adenocarcinoma, stimulates ferroptosis, and enhances their chemosensitivity to cisplatin [ 101 ].…”
Section: Ferroptosis In Cancermentioning
confidence: 99%
“…Functioning as a type 3 ferroptosis inducer, the ferroptosis-inducing agent 56 (FIN56) promotes ferroptosis by facilitating the autophagydependent protein degradation of GPX4 (Shimada et al, 2016;. FIN56 combined with cisplatin increases cellular ROS levels, decreases antioxidant gene expression, and boosts the cisplatin cytotoxic effect in the A549 cell line, indicating that inducing ferroptosis is a promising strategy in cisplatin-resistant cancer cells (Golbashirzadeh et al, 2023).…”
Section: Reversing Chemotherapy Resistance Through Inducing Ferroptos...mentioning
confidence: 99%